Caracterização molecular de Cryptosporidium spp. e ocorrência dos principais parasitas gastrointestinais em amostras fecais de cães e gatos naturalmente infectados - Alves, Marta Elena Machado (2018)
Dogs and cats are definitive hosts of innumerable parasites of the gastrointestinal tract and promote the maintenance of the biological cycle, since they eliminate eggs from helminths and cysts and protozoan oocysts, favoring the contamination of the environment and the spread of diseases. The narrowing of the interaction between pets and humans enhances human exposure to parasites with zoonotic potential, such as Ancylostoma spp., Toxocara spp., Giardia duodenalis and Cryptosporidium spp. Considering the role of companion animals in parasitic zoonoses, the objective of this work was to investigate the gastrointestinal parasitism and to characterize the species of Cryptosporidium spp. found in naturally infected dogs and cats. For this, 177 samples of feces were collected, 128 were collected from dogs and 49 from cats of both sexes and varied ages. Feces samples were obtained from animals attended at the University Veterinary Hospital (HVU) of the Federal University of Santa Maria (UFSM), Santa Maria, Rio Grande do Sul, from February to April 2017. In the analyzes using the techniques of Sheather and Faust and Ziehl Neelsen staining, one or more parasites of the gastrointestinal tract were found in 56.2% of fecal samples from dogs examined, and 53.0% of cat feces samples. In dogs Ancylostoma spp. (36.7%) was the most frequent parasite, followed by Cryptosporidium spp. (22.6%), Giardia spp. (4.6%), Cystoisospora spp. (3.1%), Taenia spp. (3.1%), Toxocara canis (3.1%), Trichuris spp. (1.5%) and Dipylidium caninum (0.7%). In cats, Cryptosporidium spp. (22.4%) was more frequent, followed by Ancylostoma spp. (18.3%), Cystoisospora spp. (16.3%), Toxocara cati (12.2%), Giardia spp. (4.0%), Spirometra spp. (4.0%), Taenia spp. (4.0%) and Toxascaris leonine (4.0%). Mononfection was identified in 70.8% of dogs and 46.1% of cats. The presence of multi-infection was observed, with occurrences of 29.2% in dogs and 53.8% in cats. In dogs there was no significant difference in the age group between groups. As for cats, 57.8% of the parasitized animals were aged between 1 and 4 years, and the risk factor was significant (p <0.05). The SSU rRNA gene of Cryptosporidium spp. was amplified in 5.6% (10/177) of the fecal samples analyzed using the Nested PCR technique and was detected in 4.6% (6/128) of the feces samples of dogs and 8.2% (4 / 49) of the cat samples. Positive samples were characterized using DNA sequencing. In dogs, C. canis (66.6% - 4/6) and C. parvum (33.3% - 2/6) and C. felis (75% - 3/4) and C. parvum (25% - 1/4). The most frequent gastrointestinal parasites in this study are agents of public health importance. In this way, the importance of the control and prevention of gastrointestinal parasitoses should be emphasized through the correct diagnosis and the use of effective drugs.